Overexpression of PvGF14c from Phyllostachys violascens Delays Flowering Time in Transgenic Arabidopsis - Li, Bingjuan; Xiao, Guohui; Luo, Kaisheng; Wang, Zhengyi; Mao, Bizeng; Lin, Xinchun; Guo, Xiaoqin (Frontiers in Plant Science, 2018)
14-3-3 Proteins are a family of highly conserved regulatory molecules expressed in all eukaryotic cells and regulate a diverse set of biological responses in plants. However, their functions in flowering of Phyllostachys violascens are poorly understood. In this study, four non-𝜀 Pv14-3-3 genes from P. violascens were identified and named PvGF14b, PvGF14c, PvGF14e, and PvGF14f. qRT-PCR analyses revealed that PvGF14b and PvGF14e exhibited widely expressed in all tested bamboo tissues. PvGF14b was highest expression in root and lowest in immature leaf. Whereas PvGF14c and PvGF14f showed tissue-specific expression. PvGF14c was mainly expressed in immature and mature leaves. PvGF14f was highest expression in mature leaves. These four genes were not significantly differentially expressed in mature leaf before bamboo flowering and during flower development. PvGF14b and PvGF14c were not induced by circadian rhythm. PvGF14c displayed subcellular localization in the cytoplasm and PvFT in nucleus and cytoplasm. Yeast two-hybrid screening and bimolecular fluorescence complementation confirmed the interaction between PvGF14c and PvFT. The overexpression of PvGF14b, PvGF14c, and PvGF14e significantly delayed flowering time in transgenic Arabidopsis under long-day condition. These findings suggested that at least three PvGF14 genes are involved in flowering and may act as a negative regulator of flowering by interacting with PvFT in bamboo.